MORPHOLOGICAL AWARENESS: STUDENTS’ ABILITY IN WORD FORMATION ANALYSIS OF READING TEXT - Andi Rizki Fauzi (English Study Program University of Pasir Pengaraian, 2015)
This research was aimed to know the students’ ability in word formation analysis of reading text and to find out what their difficulties were. Theresearch was conducted using mix method: quantitative followed by qualitative whose data taken from test and interview.The purposive sampling was chosen to select the sample consisting of 24 students. Based on the research finding, the students’ ability were quite good in three aspects of analyses: number of morpheme, content word, and function word. However, in other aspects: derivation and inflection, their abilities were so poor because the lack of knolwledge in both of aspects .